(untitled) (Revista Contexto & Educação, 2026)
Autism Spectrum Disorder (ASD) is marked by difficulties in communication and social interaction that impact the individual’s functionality. Little has been explored about the occupational perspectives of people with ASD regarding their future. The objective of this study is to understand the occupational perspectives of young people with ASD who have completed or completed high school a year ago. This is a cross-sectional qualitative study, with five young participants, between 16 and 18 years old, 3 males and 2 females, with socioeconomic levels B and C, from different cities in the Southeast region of Brazil. Semi-structured interviews were carried out in an online format treated with content analysis. The study was submitted to and approved by the Human Research Ethics Committee. The participants presented occupational perspectives of work and study similar to young people with neurotypical development, in which they aspire to enter higher education and the job market, marked by doubts regarding university courses. From access to young people with ASD to carrying out the interviews, an average of 45 days passed, requiring the presence of the mother as a mediator for participants to enter and/or remain in the research. The presence of the mothers served as comfort and security for the participants, since the researcher was an unknown figure to them. In relation to romantic relationships, young people were uncertain and unprepared for relational skills, making it difficult to immediately experience and project a relationship. Students with ASD who manage to reach high school fit the profile of lower demand for support and are cognitively able to plan the continuation of studies and insertion into work. However, they present relational difficulties that hinder or impede contact with the researcher or romantic experiences.